2021-2022 Kansas State University Industrial Hemp Cannabidiol (CBD) Research Report - Jason Griffin (Kansas Agricultural Experiment Station Research Reports, 2023)
Hemp is a broad term used to describe the many varieties of Cannabis sativa L. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently was allowed to be grown once again in the United States. Varieties have been selected and are currently grown with a wide cannabinoid profile. Cannabinoids are of high interest for their putative medical and therapeutic role in humans and companion pets. Cannabidiol (CBD) and THC are the two cannabinoids of primary interest. THC is of interest because it determines whether the final product is considered hemp (0.3% THC). CBD is of interest because of its potential therapeutic properties and its legal status across many states. Currently, there is little published information regarding best management practices to grow CBD hemp in Kansas. Controlled experiments are necessary to determine optimum production practices in Kansas. There are still many aspects of production that have not been addressed or answered in the scientific literature. Currently, growers must rely on only a limited volume of data in KS or information generated from other states with vastly different growing conditions. Variety selection, fertility management, and potting substrate characteristics are vital in CBD hemp production because environmental conditions strongly influence cannabinoid ratios and ultimately, total cannabinoid content. The objectives of these studies were to evaluate the effectiveness of a simple controlled release fertilizer and to investigate the influence of potting substrate volume on yield and quality of CBD hemp plants. Fertility recommendations for containerized hemp plants can be complicated and require expensive equipment to deliver nutrients in the prescribed ratios at the right time. A simplified fertility program could be beneficial to hemp growers. However, growers would lose the ability to rapidly adjust the fertility program to meet changing conditions in the growing area. Additionally, these plants grow rapidly during the growing season and quickly become pot-bound before harvest. A larger volume for root growth may increase yield at the end of the season. However, larger substrate volumes require greater input costs, which may not be justified by an increase in yield.
Keywords: cannabidiol; container size; controlled release fertilizer; slow release fertilizer; substrate